Causes of Dropout in Higher Education: An Analysis of Student Dropouts in Bachelor of Education from Marsyangdi Multiple Campus - Neupane, Binod (Marsyangdi Journal, 2024)
Student dropout in higher education institutions (HEIs) is a serious problem in many developed and developing countries including Nepal. According to the University Grants Commission (UGC) report, many campuses are at risk and have a low number of students due to the high dropout rate. This paper aims to analyse student dropout in B.Ed. programme at Marsyangdi Multiple Campus (MMC) and explores the main causes of high dropouts with some measuring strategies to mitigate the problem. Following a qualitative survey through telephone interviews with 30 dropout students, I collected information and analysed it thematically in a narrative way. The study's findings revealed that 65.47% of students left the campus before completing their degree. The study explored the major causes of high dropouts related to four indicators such as student, institutional, family, and community. Most students leave their studies due to financial constraints, socioeconomic factors, institutional insufficiency, employment opportunities, study abroad, and early marriage and pregnancy. The findings of the study apply to reducing the increasing number of dropouts from the university and other similar campuses. In addition to this, it implies formulating higher education policy and reforming the HEIs as per the demands of the time.